Make your own magic : a beginner's guide to self-empowering witchcraft - Lovelace, Amanda (Running Press, 2024)
"An accessible guide to incorporating magic into your life completely from scratch, welcoming beginner witches with arms wide open. As witchcraft grows ever more popular, there are countless introductions to magical practice to choose from-so many that you might not know where to begin. When you're just getting started, it's easy to be intimidated by even "entry-level" magic books, or you simply may not have time to read such heavy texts, leaving you discouraged. Make Your Own Magic aims to change that, showing that magic doesn't have to be fancy, time-consuming, or one-size-fits-all. Drawing from years of practical experience, this is an interactive beginner's guide that introduces the tenets of witchcraft so that you can develop your own practice in whatever way works for you. amanda lovelace offers simple explanations, inspiring poetry, words of encouragement, magical journaling prompts, and the tools needed to begin building a strong, long-lasting practice focused on self-love"--